Analysis of Financial Literacy Level of Fifth-Graders at Public Elementary Schools in Gondokusuman Sub-district, Yogyakarta City - Dewi, Irana; Rusmawan, Rusmawan; Susanti, Maria Melani Ika (EduBasic Journal: Jurnal Pendidikan Dasar, 2023)
Introduction to financial literacy from an early age will make children accustomed to managing finances properly and correctly in the future. This study aimed to analyze the financial literacy level of fifth-graders at public elementary schools in the Gondokusuman Sub-district. This research is a descriptive quantitative survey method. The population was 394 students, with a total sample of 196, following Krejcie Morgan’s minimum sample determination table, by using a cluster sampling technique. The data collection technique used a closed statement questionnaire. The data obtained were then analyzed descriptively. The results of this study indicate that the financial literacy level of fifth-graders was obtained from four indicators. Indicator of personal financial planning and personal financial control, on average, were at a moderate financial literacy level, with a financial literacy level of 75.74%; indicator of saving was at a high financial literacy level, with a financial literacy level of 82.03%; indicator of risk control was at a moderate financial literacy level, with a financial literacy level of 69.34%; indicator of income management and investment benefits was at a moderate financial literacy level, with a financial literacy level of 76.07%. From the accumulation of all these indicators, the resulting level of financial literacy in fifth-grade students at public elementary schools in the Gondokusuman Sub-district was 77.39%, included in the category of moderate financial literacy level. Thus, it needs to be improved by providing financial literacy knowledge, such as distinguishing between needs and wants and managing personal finances.